(untitled) (Acta Polytechnica CTU Proceedings, 2022)
Advanced porous structures are novel, emerging materials with a broad range of applicability but a rather difficult means of design and manufacturing. The advent and availability of the additive manufacturing industry in the last decade has enabled for production of these structures via 3D printing of polymers and metals. This research deals with the design, mechanical testing and preparation of FEM meshes of novel gyroid structures manufactured by PA12 SLS 3D printing. As demonstrated, conventional means of CAD generation of these structures in the *.STL format are sufficient for manufacture of specimens, but not precise enough for the purpose of mesh generation for FEM due to errors in the geometry of tesselation. Mechanical tests show that the sheet gyroid variant is the preferable geometry as it offers the greatest peak compressive stress among all variants at the same material density.